The environment and world history - Burke, Edmund, 1940-; Pomeranz, Kenneth; American Council of Learned Societies (Berkeley : University of California Press, 2009)
In 11 essays, the contributors examine the connections between envir onmental change and other major topics of early modern world history: p opulation growth, commercialization, imperialism, industrialization, th e fossil fuel revolution, and more.
Introduction : world history and environmental history / Kenneth Pom eranz -- The big story : human history, energy regimes, and the environ ment / Edmund Burke III -- Toward a global system of property rights in land / John F. Richards -- The transformation of the Middle Eastern en vironment, 1500 B.C.E.-2000 C.E. / Edmund Burke III -- The transformati on of China's environment, 1500-2000 / Kenneth Pomeranz -- The Rhine as a world river / Mark Cioc -- Continuity and transformation : colonial rice frontiers and their environmental impact on the great river deltas of mainland Southeast Asia / Michael Adas -- Beyond the colonial parad igm : African history and environmental history in large-scale perspect ive / William Beinart -- Environmental histories of India : of states, landscapes, and ecologies / Mahesh Rangarajan -- Latin American environ mental history : a shifting old/new field / Lise Sedrez -- The predator y tribute-taking state : a framework for understanding Russian environm ental history / Douglas R. Weiner.
Includes bibliographical references (p. 317-336) and index.
Electronic text and image data.
Keywords: Human ecology -- History; Nature -- Effect of human beings on -- History; Environmental sciences -- History